Physiological functions of the effects of the different bathing method on recovery from local muscle fatigue - Lee, S.; Ishibashi, S.; Shimomura, Y.; Katsuura, T. (Journal of Physiological Anthropology, 2012)
Recently, mist saunas have been used in the home as a new bathing style in Japan. However, there are still few reports on the effects of bathing methods on recovery from muscle fatigue. Furthermore, the effect of mist sauna bathing on human physiological function has not yet been revealed. Therefore, we measured the physiological effects of bathing methods including the mist sauna on recovery from muscle fatigue.